2007
DOI: 10.1111/j.1600-0684.2007.00225.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of longtail macaques (Macaca fascicularis) on the island of Mauritius: an assessment of nuclear and mitochondrial DNA polymorphisms

Abstract: We found this population to be panmictic, with a low degree of genetic variability. On the basis of an mtDNA phylogeny, we inferred that these macaques' ancestors originated from Java in Asia. Weak gametic disequilibrium was observed, suggesting decay of non-random associations between genomic genes at the time of founding. The results suggest that macaques bred in Mauritius are valuable as model animals for biomedical research because of their genetic homogeneity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
53
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 28 publications
8
53
1
Order By: Relevance
“…The Mauritian animals, purportedly introduced from Java as recently as the seventeenth or eighteenth centuries Tattersall 1981, 1986), reflect strong founder effects by exhibiting approximately one fourth of all the alleles found in long-tailed macaques and in both macaque species, respectively. The low Mauritian diversity at STR (as observed in this study as well as that by Bonhomme et al 2008), MHC (Kawamoto et al 2008) and mtDNA ) loci and the absence of Y chromosomal variation Coke 2007, Kawamoto et al 2008) have been attributed to small founder representation and subsequent rapid population expansion , Kawamoto et al 2008, Bonhomme et al 2008. In contrast to the findings here that the Mauritian and Indonesian animals are indeed genetically distinct, Bonhomme et al (2008) and Kawamoto et al (2008) reported a higher degree of similarity between the Mauritian and Javan animals suggesting that the founders of the former population actually descend from Javanese ancestors.…”
Section: Discussionmentioning
confidence: 59%
“…The Mauritian animals, purportedly introduced from Java as recently as the seventeenth or eighteenth centuries Tattersall 1981, 1986), reflect strong founder effects by exhibiting approximately one fourth of all the alleles found in long-tailed macaques and in both macaque species, respectively. The low Mauritian diversity at STR (as observed in this study as well as that by Bonhomme et al 2008), MHC (Kawamoto et al 2008) and mtDNA ) loci and the absence of Y chromosomal variation Coke 2007, Kawamoto et al 2008) have been attributed to small founder representation and subsequent rapid population expansion , Kawamoto et al 2008, Bonhomme et al 2008. In contrast to the findings here that the Mauritian and Indonesian animals are indeed genetically distinct, Bonhomme et al (2008) and Kawamoto et al (2008) reported a higher degree of similarity between the Mauritian and Javan animals suggesting that the founders of the former population actually descend from Javanese ancestors.…”
Section: Discussionmentioning
confidence: 59%
“…Distilled water as a vehicle control or the EGME solution (300 mg/kg) at a volume of 5 mL/kg was administered orally to 3 males each for 4 consecutive days. To minimize the genetic diversity related to the different origin (Kawamoto et al, 2008;Higashino et al, 2012), monkeys from both Indonesian and Chinese origins were assigned to each group. The first day of the dosing period was designated as day 1.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…As an important genetic marker, maternally-inherited mitochondrial DNA (mtDNA) warrants special attention for genetic investigations such as intraspecies variation [35], population structure [10,12,13,20,34], phylo-, population structure [10,12,13,20,34], phylo- [10,12,13,20,34], phylo-, phylogeography [5,23,26,37], and demography [24] in ma- [5,23,26,37], and demography [24] in ma-, and demography [24] in ma- [24] in main macaque species. In particular, the mtDNA control (D-loop) region is composed of �00 to 1,000 base pairs (bp) and contains hypervariable segments 1 (HVI) and 2 (HVII).…”
Section: Introductionmentioning
confidence: 99%